2019
DOI: 10.3389/fendo.2019.00706
|View full text |Cite
|
Sign up to set email alerts
|

Combination Thyroid Hormone Replacement; Knowns and Unknowns

Abstract: Hypothyroidism is common throughout the world and readily diagnosed with thyroid function tests. Management should be straightforward but appears not to be the case. Thyroid hormone replacement with levothyroxine monotherapy is the standard treatment which is effective in the majority of cases. However, 10–15% of patients established on levothyroxine do not feel their health is entirely restored and some patients prefer the addition of liothyronine. Proponents of liothyronine argue that the ratio of T3 and T4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…Dissatisfaction with treatment is a phenomenon that has been documented repeatedly among a minority of patients who are treated for hypothyroidism and is associated with persistent symptoms despite apparently adequate treatment with L‐T4, as assessed by biochemical measures 1 . Much attention has been focused in the last 20 years on attempts to improve patient outcomes by using L‐T4 + L‐T3 24 or DTE 32 . However, several randomized controlled studies have failed to demonstrate better patient outcomes with L‐T4 + LT3 combination therapy compared to L‐T4 alone 33,34 and a single randomized controlled trial found no difference between DTE and L‐T4 treatment 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissatisfaction with treatment is a phenomenon that has been documented repeatedly among a minority of patients who are treated for hypothyroidism and is associated with persistent symptoms despite apparently adequate treatment with L‐T4, as assessed by biochemical measures 1 . Much attention has been focused in the last 20 years on attempts to improve patient outcomes by using L‐T4 + L‐T3 24 or DTE 32 . However, several randomized controlled studies have failed to demonstrate better patient outcomes with L‐T4 + LT3 combination therapy compared to L‐T4 alone 33,34 and a single randomized controlled trial found no difference between DTE and L‐T4 treatment 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized controlled trials have shown that L‐T4 + L‐T3 combination treatment fails to achieve better symptom control compared to L‐T4 alone (reviewed by Taylor et al 24 ). Nonetheless, despite the evidence for lack of efficacy, some professional thyroid organizations including the British and European Thyroid Associations recommend that a trial of L‐T4 + L‐T3 may be appropriate in selected patients who complain of residual unexplained symptoms 25‐27 …”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of patients with hypothyroidism respond to levothyroxine treatment, some individuals experience persistent symptoms despite adequate serum thyroxine correction. The combined use of levothyroxine and liothyronine, a synthetic form of T 3 , has been investigated in patients who have persistent symptoms of hypothyroidism with levothyroxine monotherapy; however, there is inconsistent evidence of the superiority of combination therapy over monotherapy with levothyroxine [31,33]. Patients with elevated TSH levels are classified into two groups according to their symptoms and free T 4 level, subclinical and overt hypothyroidism; for patients diagnosed with overt hypothyroidism, thyroid replacement therapy with levothyroxine is indicated.…”
Section: Management Of Hypothyroidismmentioning
confidence: 99%
“…Although the majority of patients with hypothyroidism respond to levothyroxine treatment, some individuals experience persistent symptoms despite adequate serum thyroxine correction. The combined use of levothyroxine and liothyronine, a synthetic form of T 3 , has been investigated in patients who have persistent symptoms of hypothyroidism with levothyroxine monotherapy; however, there is inconsistent evidence of the superiority of combination therapy over monotherapy with levothyroxine [ 31 , 33 ].…”
Section: Management Of Hypothyroidismmentioning
confidence: 99%
“…Studies have shown that individuals with genetic variations in deiodinase type 2 and the thyroid hormone transporter protein MCT10 experience additional benefits with combined LT3 + LT4 therapy, though the sample size was small (3). On the other hand, single nucleotide polymorphisms may have little discriminatory power to determine which patients could benefit from combination therapy (3).…”
mentioning
confidence: 99%